PENDIDIKAN INTEGRATIF–INTERKONEKTIF; KAJIAN FILSAFAT PENDIDIKAN: Upaya Menemukan Landasan Pendidikan Integratif) - Anis Zulia A’limatun Nisa (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
The current social reality, the educational process that takes place in public education institutions and in Islamic educational institutions still separates the two subjects, namely general subjects and religious lessons. Teachers only provide general knowledge during general lessonssuch as IPA, IPS, Indonesian, and others that are general, and vice versa teachers only provide religious knowledge of religious lessons in progress. This suggests that current education still contains dichotomic views. The concept of the integrity of science that is in accordance with the Qur'an and Hadith as well as the scholars' earlier needs to be re-realized in the present era. So it is necessary to study deeply to find the basis of integrative education through philosophical study. It is an attempt to eliminate the existence of a scientific dichotomy or attempt to integrate general science "science" and religion by referring to the philosophy of education. In this study found that integrative education holistically integralistically involves the realm of philosophy; first, the ontology of "the existing essence", both in the form of real and unreal realms, in the Qur'an is contained in qouliyah, kauniyah and nafsiyah verses. Second, the epistemology of "Knowledge theory" that is, optimizing the sensory functions (sight, hearing and conscience). Third, the axiology is the realization of the benefits and blessings of science, so that will create human beings who can be responsible in the future.Key Words: integrative education, educational philosophy